FINANCIAL ANALYSIS BASED ON THE ANNUAL BALANCE - ILIE RĂSCOLEAN; ILEANA-SORINA RAKOS (Annals of the University of Petrosani: Economics, 2015)
This article demonstrates the fact that an important place in the statistical analysis of the financial management of the company goes to the analysis of the balance of assets, this representing a certain state of the capital in point of its existence, material structure and financial results obtained. It represents as well a consequence of the development of the processes forming the activity object of the company, constituting its financial framework. The balance of assets relies on the analysis liquidities-exigibility and highlights the company’s insolvency risk, namely the firm’s incapacity of honouring its commitments to third parties. The financial analysis aims to research the company’s balance statements and, especially, to measure the financial profitability starting from the balance sheet in the result account and from any other information given by the trading company or which could be obtained based on them. The authors of this article believe that by the financial analysis of the assets one can determine the net patrimony and also the accounting value of the shareholders’ shares and, respectively, one can establish the liquidity and solvency of the company, and the evaluation of the financial performances, detecting eventual situations of financial imbalance that could affect the continuity of the activity.